New Methods for the Chemical Isolation and Stable Isotope Measurement of Multiple Transition Metals, with Application to the Earth Sciences. Issue 4 (8th August 2021) - Sun, Mingzhao; Archer, Corey; Vance, Derek
Abstract : Rapid advances in multi‐collector inductively coupled plasma‐mass spectrometry have made the routine, precise and accurate measurement of metal stable isotope ratios feasible, providing an opportunity to investigate past and present geochemical processes using transition metal abundances, abundance ratios and stable isotope compositions. Many studies have stressed the matrix of different controls on different metals and highlight the potential utility of studies of multiple metals on the same samples. Here we describe a new, multi‐step chemical separation procedure that allows robust, and with blank contamination‐free, measurements of the isotope systems of the transition metals Mo, Cu, Fe, Zn and Ni at high precision from a single sample aliquot and from a range of sample types. We test the approach via the isotopic analysis of four USGS rock reference materials: two basalts (BCR‐2, BHVO‐2) and two Fe‐Mn nodules (Nod‐A1 and Nod‐P1) as well as a shale (SGR‐1). The good 'reproducibility', and the agreement between measured values and reference values where available, demonstrates the validity and efficacy of our multi‐step protocol. We also discuss in detail the key requirements of the approach, and the potential pitfalls that are encountered. Abstract : Key Points New multi‐element chemical purification procedure for transition metals with key biogeochemical properties developed from one sample aliquot. Essential to this approach is the utilisation of double spikes, which themselves are required to be pure. Methods verified using USGS geological reference materials.